Implementation and evaluation of a needs-based faculty development programme in a medical college of Pakistan: A mixed methods action-research - Qazi, Muhammad Abdullah; Aman, Fatima; Jadoon, Maidha; Rafique, Masooma; Khan, Summara; Bilal Khan, Raima (Journal of the Pakistan Medical Association, 2025)
Objective: To implement and evaluate a needs-based faculty development programme in a female-only medical college. Method: The mixed methods study was conducted in 2022-23 at the Women Medical and Dental College, Abbottabad, Pakistan. The faculty needs assessment was conducted in February 2022 using an online questionnaire, followed by identification of institutional needs through consultation in various organisational forums. Faculty development activities were planned and implemented in 2022-23 based on the needs assessment. At the end of each faculty development activity, the participants were asked to fill a feedback questionnaire. At the conclusion of the programme, 10 individual semi-structured face-to-face interviews were conducted, and the data was thematically analysed to evaluate the programme. Results: Areas including development of multiple choice questions, use of teaching aids, medical education research, curriculum development, leadership in medical education, time management, and small group interactive teaching were identified during the needs assessment phase. The total average feedback score for all activities combined was 4.2 out of 5 (SD = 0.17), with positive feedback in open-ended questions. Five core themes emerged from the interview data: teaching skills development, applicable content, needs-based programme, networking opportunities, and learner-centred activities. Conclusion: Faculty development programmes should be needs-based, and should focus on context-specific content, learner-centred activities and networking opportunities. Continuous evaluation of the programme is an important element. Key Words: Faculty, Needs assessment, Capacity-building, Education, Medical.